Oral microbiome and preterm birth - Vidmar Šimic, Marijana; Maver, Aleš; Zimani, Ana Nyasha; Hočevar, Keli; Peterlin, Borut; Kovanda, Anja; Premru-Sršen, Tanja (Frontiers in Medicine, 2023)
Background The etiology of preterm birth (PTB) is heterogeneous and not yet well known. Maternal periodontal disease has been investigated for decades and is a known risk factor for adverse pregnancy outcomes. However, no particular bacterial species or higher taxonomic order has been found as causative of PTB, leading to studies of the whole oral microbiome. In order to determine if and how the composition of the oral microbiome is associated with PTB, we performed a large case–control study including women with term (TB) and PTB. Methods We compared oral microbiomes in PTB to TB, to examine differences in the microbial richness, diversity, and differential abundance of specific taxa. We obtained oral swab samples from 152 Caucasian pregnant women who were classified as either PTB (≤36 6/7 weeks, n = 61) or TB (≥38 0/7 weeks, n = 91) in exclusion of any other major medical or obstetric conditions. The oral microbiomes of these women were characterized by 16S ribosomal RNA (rRNA) gene sequencing of the V3–V4 region on the MiSeq platform. Results The dominant microorganisms at the phylum level in all pregnant women regardless of birth week outcomes as belonging to Firmicutes, Proteobacteria, Bacteroidetes, Fusobacteria, and Actinobacteria. The phyla Firmicutes and Bacteroidetes were relatively more abundant in women with a PTB than in women with a TB, while Proteobacteria was less prevalent in women with a PTB. At the genus level, Veillonella, Prevotella, and Capnocytophaga were enriched in the PTB, and while many of the members of these genera could not be resolved to the species level, Veillonella massillensis was shown to be increased in the PTB group. Conclusion We identified the genera Veillonella, Prevotella, and Capnocytophaga in the maternal oral microbiome as being associated with PTB independently of clinically apparent infection, uterine anomalies, and other pregnancy complications, including placenta previa, and placental abruption. The clarification of the role of those taxa in the etiology of PTB merits further research.